PTU-108 Azathioprine Pharmacogenetics in Autoimmune Hepatitis. (4th June 2013) - Dhaliwal, H; McFarlane, E; Gleeson, D; Lennard, L
Abstract : Introduction: Azathioprine (AZA) is widely used to treat autoimmune hepatitis (AIH). However, 20% of patients are intolerant of AZA and a further 18% are unresponsive. AZA metabolism is complex and in childhood leukaemia, genetic polymorphisms in thiopurine methyltransferase (TPMT) and inosine triphosphate pyrophosphatase (ITPA) have been associated with AZA toxicity and differences in active metabolite production. This has been little studied in AIH. We aimed to assess the association of these polymorphisms with AZA toxicity and with accumulation of AZA derived thioguanine nucleotide (TGN) and methylmercaptopurine metabolites (MeMPNs) in AIH. Methods: We studied 151 patients with AIH (123 female; median age at diagnosis 55 (range 2–81) years). Subjects were genotyped for the presence of TPMT *3, TPMT *2 and ITPA (94C > A and IVS2+21A > C) variant alleles. TGNs and and MeMPNs were measured in patients who remained on AZA. Results: For TPMT, 138 patients were wildtype and 13 (9%) were heterozygous (1 TPMT*2, 11 TPMT*3A and 1 TPMT*3C ). For ITPA, 95 were wildtype, 50(33%) heterozygous (10 94C > A and 40 IVS2+21A > C) and 6 homozygous/compound heterozygous. There were 57 adverse events (AE) in 54(36%) patients – in 32 (21%) AZA was withdrawn. TPMT wildtype and heterozygous patients had a similar incidence of leucopenia (18 vs 17%, p = 0.9 ) and of non-myelotoxic AEs (21 vs 8% p = 0.5). Likewise, ITPA wildtype, heterozygous and homozygous patients had a similar incidence of leucopenia (19, 10 and 16% respectively, p = 0.2) and of non-myelotoxic AEs (20, 39 and 15%, p = 0.2). Compared to wildtype patients, TPMT heterozygotes accumulated higher concentrations of TGNs (413 vs 212 pmol/8x108RBCs, p = 0.009) and lower MeMPNs (111 vs. 1000 pmol/8x108RBCs, p < 0.001), despite being a lower doses of AZA (1.0 vs. 1.7 mg/kg/day, p < 0.001). Comparing IPTA wildtype, heterozygous and homozygous patients, there was no difference in TGNs (222, 212 and 176 pmol/8x108 RBCs respectively, p = 0.76) and MeMPNs (957, 957 and 713 pmol/8x108RBCs respectively, p = 0.7) Conclusion: TPMT and ITPA polymorphisms do not predict the occurrence of adverse events in AIH. However, TPMT genotyping may be clinically useful as heterozygous patients may require a lower dose of AZA. Disclosure of Interest: None Declared